Ultrathin nitrogen-doped graphitized carbon shell encapsulating CoRu bimetallic nanoparticles for enhanced electrocatalytic hydrogen evolution. (5th April 2018) - Xu, You; Li, Yinghao; Yin, Shuli; Yu, Hongjie; Xue, Hairong; Li, Xiaonian; Wang, Hongjing; Wang, Liang
Abstract: Design of highly active and cost-effective electrocatalysts is very important for the generation of hydrogen by electrochemical water-splitting. Herein, we report the fabrication of ultrathin nitrogen-doped graphitized carbon shell encapsulating CoRu bimetallic nanoparticles (CoRu@NCs) and demonstrate their promising feasibility for efficiently catalyzing the hydrogen evolution reaction (HER) over a wide pH range. The resultant CoRu@NC nanohybrids possess an alloy–carbon core–shell structure with encapsulated low-ruthenium-content CoRu bimetallic alloy nanoparticles (10–30 nm) as the core and ultrathin nitrogen-doped graphitized carbon layers (2–6 layers) as the shell. Remarkably, the optimized catalyst (CoRu@NC-2 sample) with a Ru content as low as 2.04 wt% shows superior catalytic activity and excellent durability for HER in acidic, neutral, and alkaline conditions. This work offers a new method for the design and synthesis of non-platium-based electrocatalysts for HER in all-pH.